2020
DOI: 10.1186/s12872-020-01743-3
|View full text |Cite
|
Sign up to set email alerts
|

Differential leukocyte counts and cardiovascular mortality in very old patients with acute myocardial infarction: a Chinese cohort study

Abstract: Background Total leukocyte and differential Leukocyte counts are prognostic indictors in patients with coronary artery disease (CAD). However, there is no data available regarding their prognostic utility in very old patients with acute myocardial infarction (AMI). The aim of this study is to investigate the potential role of different leukocyte parameters in predicting the mortality among very old patients with AMI. Methods A total of 523 patients aged over 80 years with AMI were consecutively enrolled into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Previous studies have suggested that advanced age, chronic kidney disease, and HF are related to inflammatory response status and associated with higher mortality of AMI patients ( 31 , 32 ). Yan et al found that NLR was a potential independent marker of mortality in elderly patients with AMI, which was consistent with our subgroup analysis ( 33 ). Physicians need to be vigilant in AMI patients with high- and very high-NLR, especially those with advanced age, higher SCr and WBC concentrations, HF, and those without reperfusion therapy.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have suggested that advanced age, chronic kidney disease, and HF are related to inflammatory response status and associated with higher mortality of AMI patients ( 31 , 32 ). Yan et al found that NLR was a potential independent marker of mortality in elderly patients with AMI, which was consistent with our subgroup analysis ( 33 ). Physicians need to be vigilant in AMI patients with high- and very high-NLR, especially those with advanced age, higher SCr and WBC concentrations, HF, and those without reperfusion therapy.…”
Section: Discussionsupporting
confidence: 92%
“…In elderly patients with AMI, NLR is significantly and independently related to mortality, and has better predictive power than other leukocyte parameters. Moreover, adding NLR to traditional risk models, including age, hypertension, diabetes and other risk factors, also significantly improves the efficiency of the model 21 . Recent studies have found that in acute coronary syndromes, the NLR value is related to the prognosis of ACS.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in newly diagnosed multiple myeloma patients who received bortezomib+cyclophosphamide+dexamethasone regimen therapy, Pang et al ( 7 ) found that the high NMLR group experienced a lower median progression-free survival than the low NMLR group. In addition, in very old patients (>80 years old) with AMI, Yan et al ( 8 ) suggested that NMLR appeared to be an independent marker for long-term cardiovascular mortality.…”
Section: Discussionmentioning
confidence: 99%
“…As an emerging indicator of inflammatory and immune status, NMLR is the ratio of the sum of peripheral neutrophil and monocyte counts to peripheral lymphocyte counts. Although a few previous studies have suggested that NMLR is a prognostic indicator for diseases related to inflammatory and immune disorders ( 7 , 8 ), evidence supporting the association between admission NMLR and in-hospital mortality in AMI remains scarce. Given that NMLR integrates different acute-phase inflammatory and immune responses and may comprehensively reflect the balance between damage and repair in AMI, we hypothesized that admission NMLR might represent a powerful predictor for in-hospital mortality in AMI.…”
Section: Introductionmentioning
confidence: 99%